Entrepreneurial Leadership: An Exploratory Study of Attitudinal and Behavioral Patterns over the Business Life-Cycle - Kesidou, Eleni; Carter, Sara (Senate Hall, 2018)
Strategic approaches to venture creation and development highlight the importance of entrepreneurial leadership to business success, yet remarkably little is known about what entrepreneurial leaders actually do and why they do it. This study addresses these key questions through detailed analysis of six case companies, each with multiple informants reflecting on critical incidents experienced over the business life-cycle. Contextual depth is achieved by going beyond cross-sectional investigation taking a chronological lens to the temporal dimensions of behaviors characterizing entrepreneurial leadership. This approach produced novel insights into the evolving nature of entrepreneurial leadership showing that entrepreneurial leaders transit from influencing to enabling behaviors as they move from the pre-organizational to the organizational phase of the business life-cycle. The findings contribute towards the conceptual elucidation of entrepreneurial leadership as a leadership style and help unpack the choice of entrepreneurial leadership as a strategic approach to entrepreneurship. Keywords: entrepreneurial leadership, organizational emergence, critical incident technique, business life-cycle
Keywords: entrepreneurial leadership|organizational emergence|critical incident technique|business life-cycle